О приспособлениях некоторых видов дуплогнездных птиц к защите потомства от эктопаразитов - Коваль, Н.Ф. (Вестник зоологии, 1971)
It wa s established that when making nests starlings use green shoots and potato
and potato leaves and tree sparrows — wormwood as a construction material. It is supposed that birds use these plants In connection with their phytoncide properties to disinfect nest chambers from ectoparasites. Adaptive peculiarities of progeny protection from
cctoparazites are also considered in some other hollow-nesting birds.